ASPEK PREDISPOSISI FAKTOR TERHADAP PERILAKU PEMBERANTASAN SARANG NYAMUK (PSN) - Ngambut, Karolus; Kaliky, M Fadly; Nuryatna, Dedih; Rina, Wa (Ensiklopedia of Journal, 2024)
Abstract: Dengue fever (DHF) remains a serious threat to public health, even though it is not a new disease. Every year, many cases of DHF continue to be reported in various regions, indicating that existing prevention and control efforts have not been fully effective. The purpose of the study was to determine the predisposing factors to mosquito nest eradication (PSN) behavior. The research design used in this study was cross sectional. The research was conducted in November 2023 in Rajabasa District. The population was all families residing in Rajabasa Sub-district, totaling 10,101 families. The sample amounted to 91 families selected using proportional simple random sampling. The research instrument used a research questionnaire. Data were analyzed univariately and bivariately. The results showed that there was a relationship between knowledge (p value: 0.013) and attitude (p value: 0.007) with mosquito nest eradication behavior. It is recommended for health workers to continue intensive counseling on PSN as an effort to prevent DHF either directly with tools such as pictures, flipcharts, or videos so that people are more interested and understand or indirectly through stickers, billboards, and leaflets.Keywords: Mosquito Nest Eradication, Knowledge, Attitude.